Prevention of Selective Jamming Attacks Using Swarm intelligence Packet-Hiding Methods (International Journal of Engineering and Computer Science, 2013)
Jamming is one of the most dangerous Pre-arranged disturbance attacks in wireless medium. This attack with wirelesstransmission is used as a launch pad for rising Denial-of-Service attacks on wireless networks. Usually, electronic jamming hasbeen reportable as AN external threat model. We tend to take into account a sophisticated soul WHO is conscious of networksecrets and also the implementation details of network protocols at any layer within the network stack. The soul uses his internalinformation for launching jam attacks within which specific messages of “high importance” are targeted. To diminish such formsof attacks, we tend to develop 3 schemes that forestall classification of transmitted packets in real time. Our schemes suppose thejoint thought of crypto graphical mechanisms with PHY-layer attributes. However during this technique it doesn't prevent theimportant time packet classification. So, we tend to propose swarm based mostly defense technique for electronic jamming attacksin wireless sensing element networks. Swarm intelligence algorithmic program is capable to regulate amendment in topology andtraffic. In channel hoping technique, the transmitter and receiver alter the channels so as to remain far away from the transmitter.